(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The study demonstrates that the Internet, as an information dissemination tool, holds significant quantitative and qualitative advantages over traditional media. Its advantages include unlimited spatial and temporal coverage, information accessibility, ease and speed of communication, interactivity, and more. The purpose of the article is to analyze the role of new media in promoting the concept of corporate social responsibility (CSR) by presenting the results of an empirical study on the use of websites by enterprises. It has been established that CSR is based on the assumption that companies voluntarily take measures to improve the lives of stakeholders and environmental quality. Methods. The Internet acts as a social environment, changing the relationship between sender and receiver of information, with the latter becoming an equal partner in public dialogue. Results. CSR is a pro-social activity, with all measures taken voluntarily and directed toward specific stakeholders. The Internet enables the individualization of information, making it no longer impersonal. Based on the research, it was found that on CSR-related websites, the amount of CSR content is generally medium or small on most sites; the coverage of issues on company websites was mostly extensive; the content was mainly informational, with some instances being informational-problematic; materials were characterized by high coherence and clarity; most of the analyzed websites included an organizational mission; and the language was simple and understandable. The analysis of internet portals showed that the amount of CSR-related content was high, with transparency and consistency in the content; problem-informative texts predominated; the language used was clear and understandable; and the published messages were potentially highly effective. Conclusions. The portals facilitated two-way communication and included libraries and educational portals and pathways. Half of the portals had an English-language version, and most pages contained advertisements. The overall appeal of the portals was higher compared to websites. Keywords: corporate social responsibility, new media, advantages of new media, internet portals, company websites, spatial and temporal coverage.